Increased storage and secretion of phosphatidylcholines by senescent human peritoneal mesothelial cells - Bartosova, Maria; Pichl, Sebastian; Okun, Jürgen G.; Straub, Beate Katharina; Schmitt, Claus P. (Clinical and experimental nephrology, 2016)
Background/aimsHuman peritoneal mesothelial cells (HPMC) secrete phosphatidylcholines (PC) which form a lipid bilayer lining the peritoneum. They prevent frictions and adhesions and act as a barrier to the transport of water-soluble solutes while permitting water flux. PC may play an essential role in peritoneal integrity and function, the role of PD induced HPMC senescence on PC homeostasis, however, is unknown.MethodsHPMC cell lines were isolated from four non-uremic patients. Expression of the three PC synthesis genes (rt-PCR), and cellular storage and secretion of PC (ESI-mass-spectrometry) were analyzed in young and senescent HPMC (Hayflick-limit).ResultsSenescent cells displayed significantly altered morphology; flow cytometry demonstrated extensive staining for senescence-associated beta galactosidase. Nine different PC were detected in HPMC with palmitoyl-myristoyl phosphatidylcholine (PMPC) being most abundant. In senescent HPMC mRNA expression of the three key PC synthesis genes was 1.5-, 2.4- and 6-fold increased as compared to young HPMC, with the latter, phosphatidylcholine cytidylyltransferase, being rate limiting. Intracellular storage of the nine PC was 75-450 % higher in senescent vs. young HPMC, PC secretion rates were 100-300 % higher. Intracellular PC concentrations were not correlated with the PC secretion rates. Electron microscopy demonstrated lamellar bodies, the primary storage site of PC, in senescent but not in young cells.ConclusionSenescent HPMC store and secrete substantially more PC than young cells. Our findings indicate a novel protective mechanism, which should counteract peritoneal damage induced by chronic exposure to PD fluids.